Student registration management system - Lizawati, Mohamad Halit (2006)
Development in the world of computer technology nowadays introduced different new method that is useful towards individual.The computer is getting more important in all different fields and our life in this decade.In conjunction to it, a redesign system will be developing to equip the system now.Student registration management system will be developing to help student to register in any college without wasting time to filling form manually.This system also will help marketing department of Kolej Teknologi Timur to ease their work on registering new student to the database.This system was developed online and it's using software like Macromedia Dreamweaver MX and Microsoft Access 2003.